Revealing the Motives for Academic Cheating Among Students Bima College of Economics Through Approach Fraud Triangle - Alwi; Ismunandar (Journal AGENCY, 2025)
Academic fraud is a growing concern in higher education, particularly among students majoring in finance and accounting, who are expected to uphold high standards of integrity. This study aims to examine the influence of academic pressure, opportunity, and rationalization—components of the Fraud Triangle theory—on academic cheating behavior among students at the Bima College of Economics (STIE Bima). Utilizing a quantitative approach, data were collected from 170 undergraduate students in the Financial Management concentration using purposive sampling and an online questionnaire. The study employed multiple linear regression analysis with the support of SPSS version 27. The results indicate that academic pressure, opportunity, and rationalization each have a positive and statistically significant effect on academic fraud behavior. The model explains 61% of the variance in academic fraud, underscoring the critical role of psychological and contextual factors in shaping unethical academic practices. These findings highlight the need for stronger institutional controls, ethical education, and awareness programs to mitigate academic dishonesty. This study contributes to the limited body of literature applying the Fraud Triangle framework in academic settings, particularly in the Indonesian context.